KORELASI TARIAN CAKALELE SUKU ABUI DAN KONSEP PERANG ROHANI DALAM ALKITAB PERTUMBUHAN IMAN KRISTEN DI ALOR - Malaimoi, Yupither (Jurnal Teologi RAI, 2024)
In this article, the author will discuss the correlation between the Cakalele Dance of the Abui Tribe and the Concept of Spiritual War in the Bible for the Growth of Christian Faith in Alor. The concept of war in the Bible is seen a major part of protecting oneself from spiritual attacks and as part of God's people. This is based on God's Word to Moses, that faith leads believers to God's power which surpasses human power. It turns out that understanding the concept of war is not only owned by the Israelites, but also in the growth of faith. Because in this increasingly developing era, it is important to communicate the culture of the Abui tribe in Alor district. By using qualitative research methods complemented by a literature study approach, this research produces an understanding that the Cakalele dance for the Abui tribe is a culture that marks them as God's people. So there is a spiritual meaning in the cultural content of the Abui tribe's cakalele dance with the concept of spiritual war in the Bible, so that the Cakalele dance is absolute for the community in the growth of the Christian faith in Alor.